Rural Development: Sine qua non of national development - North, Liisa L. (2007)
This article deals synthetically with: first, the historical relations of economic and  social  power  at  the  national  level  that  have  created  obstacles  to  rural development in Latin America; second; the importance of rural development with  reference  to  the  persistence  of  social  inequalities  –rooted  in  the  countryside–  that  explain  lacks  in  national  development  processes  in  the  region;  third, some of the international dimensions of contemporary rural conflicts; and finally, some general recommendations for the formulation of alternative policies to replace the dogmatic implementation of the neo-liberal recipes that have caused tremendous damage in the rural areas of the third world.